Participation Of Indonesian Citizens In Elections Abroad 2019 Perspective of Maqasid Syari'ah - Maharani Ayu Lestari; Irwansyah Irwansyah (UNIVERSITAS PAKUAN, 2023)
Election implementation is essentially a way of selecting someone to fill a political position in the constitution. It is hoped that the election will produce aspirational, high-quality leaders who are especially able to bring the government closer to the people. However, in practice, facts were found related to the enthusiasm of the people for the election process and election results, where people are less enthusiastic and even hurt democratic values. Especially in the implementation of elections conducted abroad. The lack of public participation abroad in the implementation of elections is caused by their identity not being registered as the Permanent Voters List (DPT) and the long distance to the polling place (TPS). The loss of their rights is the same as the violation of basic human rights for them and this clearly violates the Maqasid Shari'ah concept, in which citizens cannot exercise their rights al-darruriyyat. This study uses the method This research uses the Normative Juridical method in which this research refers to the legal norms contained in the Legislation. The data used was obtained through a literature study. From the research conducted, it can be understood that in Law No. 7 of 2017 concerning General Elections, matters related to election procedures abroad are regulated, where the participation of Indonesian citizens living abroad is a form of fulfillment of constitutional rights and also in the view of maqasid syari'ah elections are important to be implemented in the implementation of elections abroad.